Impacto da saúde bucal na qualidade de vida de crianças e adolescentes e na rotina familiar: percepção dos pais ou responsáveis. - Chicória, João Victor Gênova [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The main recurrent oral pathologies in Brazil are dental caries and malocclusions. These evils cause many negative aspects in the lives of children and adolescents. Facing these findings, the objective of this study was to analyze the family profile, oral hygiene, prevalence of dental caries and malocclusion in children and adolescents at social risk of a charitable association of a northwestern city of São Paulo State. In addition, to verify the perception of parents or guardians over the impact of oral diseases on their children's quality of life and family routine. The registration form of the families of the children and adolescents of the project was analyzed to observe their socioeconomic profile. The oral hygiene of children and adolescents was observed through the calculation of the Simplified Oral Hygiene Index. An epidemiological survey of dental caries and treatment needs was performed using the DMF-T, dmf-t and Need for Treatment indices. The Malocclusion Index and Dental Aesthetic Index (DAI) were used to verify the presence of tooth-facial abnormalities. The Parental - Caregiver Perceptions Questionnaire (P-CPQ) was applied to evaluate the parents or guardians perceptions about the impact of oral diseases on children, and the Family Impact Scale (FIS) questionnaire, to observe the impact that oral and orofacial diseases of adolescents has on family routine. The collected data were entered into an Excel spreadsheet, tabulated and analyzed using Epi Info ™ 7.2 and BioEstat 5.0 softwares. In most cases, the respondents had two siblings (29.6%), lived in five people in the house (31.3%) and lived without the presence of the father or stepfather (54.2%). The mother (60.9%) and the father (41.3%) had low education, having studied until incomplete high school; family income was between 1 and 2 minimums (45.8%). Most of the population studied had the level of hygiene in the “regular” range (66.7%). 44 (31.9) and 67 (48.5%) of respondents had the DMF-T and dmf-t indexes greater than 0, respectively; being the decayed component the highest percentage in both indexes. In most cases, the need for treatment was restoration of one or more dental surfaces. In addition, most had dento-facial abnormalities to varying degrees (61.6%). Regarding the P-CPQ questionnaire, 35 (44.9%) of the parents answered that their child's general well-being was affected “not at all” or “only a bit” by the condition of their teeth, lips, jaws or mouth. Regarding FIS, the subscale that most interfered with family routine was “Parent / Family Activity”. The participants of the social project are families of low socioeconomic status, and are inserted in an environment that makes the prevention of diseases difficult. They have deficient hygiene and a high prevalence of dental caries and malocclusion. Parents' perception of the impact of oral diseases on their children's quality of life is low, and the most remembered subscales were “emotional well-being” and “oral symptoms”. In addition, oral diseases have an impact on family routine, especially on “parent / family activities”.

As principais patologias bucais recorrentes no Brasil são a cárie dentária e as maloclusões. Esses males ocasionam muitos aspectos negativos na vida das crianças e adolescentes. Frente a estas constatações, objetivou-se neste estudo analisar o perfil familiar, a higienização bucal, prevalência de cárie dentária e de maloclusão nas crianças e adolescentes em situação de risco social de uma associação beneficente de um município do noroeste do Estado de São Paulo. Além disso, verificar a percepção dos pais ou responsáveis em relação ao impacto das doenças bucais na qualidade de vida dos filhos e na rotina familiar. Analisou-se a ficha de cadastro das famílias das crianças e adolescentes do projeto para observar operfil socioeconômico das mesmas. Observou-se a higienização bucal dascrianças e adolescentes por meio do cálculo do Índice de Higiene Oral Simplificado. Realizou-se levantamento epidemiológico de cárie dentária e necessidades de tratamento por meio dos índices CPO-D, ceo-d e de Necessidade de Tratamento. Utilizaram-se os Índices de Maloclusão e de Estética Dental (DAI) para verificar a presença de anormalidades dento-faciais e aplicou-se o questionário Parental – Caregiver Perceptions Questionnaire (P-CPQ), para avaliar as percepções dos pais ou responsáveis sobre o impacto das doenças bucais nos filhos e o questionário Family Impact Scale (FIS), para observar o impacto que as doenças bucais e orofaciais dos adolescentes apresentam na rotina familiar. Os dados coletados foram digitados em planilha Excel, tabulados e analisados por meio dos programas Epi Info™ 7.2 e BioEstat 5.0. Na maioria dos casos, os pesquisados apresentavam dois irmãos (29,6%), moravam em cinco pessoas na casa (31,3%) e sem a presença do pai ou com o padrasto (54,2%). A mãe (60,9%) e o pai (41,3%) apresentavam baixa escolaridade, tendo estudado até o ensino médio incompleto, a renda familiar era entre 1 e 2 mínimos (45,8%). A maior parte da população estudada tinha o nível de higienização na faixa “regular” (66,7%). 44 (31,9) e 67 (48,5%) dos pesquisados apresentavam o índice CPO-D e ceo-d maior que 0, respectivamente; sendo o componente “cariado” o de maior porcentagem em ambos os índices. Na maioria dos casos, a necessidade de tratamento era restauração de uma ou mais superfícies dentais. Além disso, a maior parte apresentava anormalidades dento-faciais em diferentes graus (61,6%). Em relação ao questionário P-CPQ, 35 (44,9%) dos pais responderam que o bem-estar geral do filho era afetado “nem um pouco” ou “só um pouquinho” pela condição de seus dentes, lábios, maxilares ou boca. Quanto ao FIS, a subescala que mais interferiu na rotina familiar foi “Atividade dos pais/família”. Os participantes do projeto social integram famílias de baixo nível socioeconômico, e estão inseridos em um ambiente que pode dificultar a prevenção de doenças. Apresentam deficiência na higienização e alta prevalência de cárie dentária e maloclusão. A percepção dos pais sobre o impacto das doenças bucais na qualidade de vida dos filhos é baixa, sendo que as subescalas mais lembradas foram “bem estar emocional” e “sintomas bucais”. Além disso, as doenças bucais apresentam impacto na rotina familiar, em especial nas “atividades dos pais/família”.
Impact of oral health on the quality of life of children and adolescents and on Family routine: parents 'or guardians' perception.
Keywords: Dental caries; Malocclusion; Relações familiares; Crianças; Relações pais-filho; Cárie dentária; Má oclusão; Qualidade de vida